181k views
0 votes
-2(-3x + 4) + 3x – 3
-29

User Felipecao
by
5.2k points

2 Answers

5 votes

Answer:

11

Step-by-step explanation:

User Geoffrey Booth
by
5.9k points
5 votes

Answer:

Here

Step-by-step explanation:

Step-by-step explanation:

First, divide each side of the equation by

3

to eliminate the parenthesis while keeping the equation balanced:

3

(

3

x

4

)

=

42

3

(

3

x

4

)

3

=

42

3

3

(

3

x

4

)

3

=

14

3

x

4

=

14

Next, add

4

to each side of the equation to isolate the

x

term while keeping the equation balanced:

3

x

4

+

4

=

14

+

4

3

x

0

=

18

3

x

=

18

Now, divide each side of the equation by

3

to solve for

x

while keeping the equation balanced:

3 x 3 = 18 3

3

x

3

=

6

x

=

6

User Gaket
by
5.9k points